The crystallinity and hardness properties of Al-Cu/SiCp new composite materials - Arifutzzama, A.; Maleque, M.; Debnath, Sujan (Trans Tech Publications, Switzerland, 2012)
The main aim of this paper is to investigate the crystallinity and hardness properties of Al-Cu/SiCp matrix composite (AMC) materials. The materials were prepared using a noble stir casting technique by varying the percentage of Cu in the Al-Cu matrix. Qualitative X-ray analysis has been carried out to characterize the crystallinity of the Al-Cu/SiCp as-cast composite materials. Sample was cut and shaped into 25 mm×15 mm×4 mm in dimension then polished with diamond paste. X-ray diffraction diagrams were recorded using a transmission technique with a SHIMADZU Lab X (XRD-6000) X-ray generator operating at Cu Kα1 radiation. Hardness test was conducted using Vickers hardness tester (Mitutuyo, MVK-H2). The results indicated that a significant crystal growth was occurred in the composite materials due to increase of Cu from 2 to 4 % whereas a slight improvement of crystallinity was observed when the Cu percentage was increased from 4 to 6 % in the matrix. It was also revealed from the result that a similar trend was grasped in hardness increment with the crystallinity of Al-Cu/SiCp AMCs.